The influence of motivational climate on the physical activity adherence among junior high school students: The mediating effect of achievement goal orientation. - Ning Yang; Haiying Quan; Zimeng Guo (PLoS ONE, 2024)
In this study, which was based on the theories of motivational climate and achievement goal orientation, an experimental intervention was conducted on 82 junior high school students using the Motivational Climate Scale (MCSYS), Task and Ego Orientation in Sport Questionnaire (TEOSQ), and Physical Activity Persistence Scale. The aim was to explore the influence of different motivational climates in physical education classes on the physical activity adherence among junior high school students and examine the mediating role of achievement goal orientation. The results revealed the following significant findings: Firstly, there was a noteworthy positive correlation between the physical activity adherence among junior high school students, the motivational climate, and achievement goal orientation. Additionally, it was discovered that achievement goal orientation partially mediated the relationship between the motivational climate and the physical activity adherence among junior high school students. Secondly, it was observed that the effectiveness of improving the physical activity adherence among junior high school students increased with the duration of the experimental intervention. Lastly, it was found that the mastery climate group had a more pronounced effect on improving the physical activity adherence among junior high school students when compared to the performance climate group. These findings suggest that creating a motivational climate in physical education classes has the potential to modify the achievement goal orientation of junior high school students, subsequently enhancing their consistency in engaging in physical activity.